Simultaneous Quantitative Determination of Six Caffeoylquinic Acids in Matricaria chamomilla L. with High-Performance Liquid Chromatography - Yifan Zhao; Peng Sun; Yue Ma; Kun Wang; Xiaoqiang Chang; Yue Bai; Dong Zhang; Lan Yang (Journal of Chemistry)
A simple and effective method for the simultaneous quantitative analysis of six caffeoylquinic acids (CAs) in Matricaria chamomilla L. (M. chamomilla) using high-performance liquid chromatography (HPLC) with diode-array detection (DAD) was established. The chromatographic separation was performed on a Waters XBridge Shield RP C18 column (4.6 mm × 250 mm, 5 μm) with the mobile phase of acetonitrile (0.5% phosphoric acid) and water (0.5% phosphoric acid) using a gradient elution at a flow rate of 1.0 mL/min and UV detection at 327 nm. The correlation coefficients of all analytes were 0.999, and the results showed excellent linearity. The lower limits of detection (LLOD) and quantification (LLOQ) of all analytes fall within the range of 0.014∼0.017 μg/mL and 0.068∼0.086 μg/mL, respectively. The extraction recoveries of all analytes fall within the range of 100.74%∼101.55%, with relative standard deviation not exceeding 2.83%. The intraday and interday precisions fall within the range of 0.03%∼0.65% and 0.02%∼0.09%, respectively. This validated method was successfully applied to the investigation of 34 samples of M. chamomilla collected from different geographical areas. The results showed that the established method is appropriate for the analysis of the six CAs in M. chamomilla and helpful for quality assessment of capitula of M. chamomilla (CMC), whole herb of M. chamomilla (WHMC), and related herbal formulas.